GALT 유전자의 복합 이형 돌연변이에 의한 전형적 갈락토오스혈증 1례 - 전종근(Chong Kun Cheon); 조민성(Min Sung Cho); 고정민(Jung Min Ko); 김구환(Gu-Hwan Kim); 유한욱(Han-Wook Yoo) (Journal of genetic medicine, 2008)
Classical galactosemia is an autosomal recessive disorder of galactose metabolism, caused by a deficiency of the enzyme galactose-1-phosphate uridyltransferase (GALT). Buildup of galactose-1-phosphate is toxic at high levels and can damage the liver, brain, eyes, and other vital organs. The case presented here was that of an 11-day-old female infant who had elevated galatose levels upon initial neonatal screening test with persistent cholestatic jaundice, coagulopathy, and hepatomegaly. The patient was transferred due to aggravation of clinical symptoms including bleeding and jaundice. She had a delayed galactose free diet because of an inappropriate diagnosis. We quickly provided her with a lactose/galactose-restricted diet as per her final diagnosis. Clinical and laboratory results were improved after a few days of treatment. For confirmatory testing for classical galactosaemia, we simultaneously analyzed for GALT enzyme activity and allele-specific PCR/fragments for seven mutations and two polymorphisms in the GALT gene. We were able to find several GALT-deficient and compound heterozygous mutations of the GALT gene. 전형적 갈락토오스혈증(classical galactosemia)은 상염색체 열성으로 유전되는 galactose-1-phosphate uridyltransferase(GALT) 효소의 결핍에 의한 갈락토오스 대사 장애 질환이며 galactose-1-phosphate가 축적되어 간, 뇌, 신경에 심각한 영향을 끼친다. 본 증례는 GALT 효소 결핍 신생아에서, 출생 후 락토오스가 함유된 일반 수유를 시작하면서 심한 황달, 구토, 심한 출혈경향 및 간 부전 등이 발생하였다. 신생아 선별검사에서 갈락토오스의 증가로 재검을 의뢰하였고, 그 사이에 일반수유로 인해 임상증상이 악화 되어 생후 11일째 본원으로 전원되었다. 효소분석검사와 유전자검사로 확진 전에 임상적으로 갈락토오스혈증이 의심이 되어 소이 분유로 수유를 시작하였고, 이후 심한 황달과 출혈경향의 호전, 간기능 호전, 체중 증가와 전신상태가 회복되어 11일간의 입원 이후 퇴원하였다. 갈락토오스혈증의 임상 증상에 대한 올바른 이해를 통해 조기 진단하여 식이요법 등의 치료로 사망률을 줄이고, 유전자검사로 갈락토오스혈증을 확진하여 유전상담 및 산전진단에 유용하게 이용할 수 있는데, 본 증례에서는 효소분석 결과 GALT 효소 결핍증과 유전자검사에서 아직까지 보고된 적이 없는 GALT 유전자의 이형 돌연변이를 경험 하였기에 이를 보고하는 바이다.